Does Soil Organic Matter Affect the Impact of the Ionic Liquid Ethylammonium Nitrate in the Pure State and as Mixture with Lithium Salt on Basal Soil Respiration? - Sixto, Teresa (2020)
Although ionic liquids (ILs) do not contaminate the atmosphere (because of their low vapourpressure), they may have toxic effects in aquatic and terrestrial environments. Therefore, beforeILs can be widely used for different applications, their toxicity must be tested in different environments.The IL ethylammonium nitrate (EAN) is of interest in electrochemical applications, and research is currently underway to investigate the electrochemical activity of mixtures of this compound with inorganic salts. In this study, we investigated the impacts of different amounts of pure EAN and of mixtures of EAN and lithium salt on basal soil respiration in two soils differing in organic matter content.